Evaluation of conformities of producers of the Cerrado of Minas Gerais, Brazil, with the norm of integrated coffee production - Santos, Júlio César Freitas; Raij, Bernardo van; Lima, Aguinaldo José de; Júnior, Paulo César Afonso (Coffee Science - ISSN 1984-3909)
Integrated Coffee Production ICP is a norm developed with the purpose to insert coffee production in the modern concept of sustainable development, can be used by coffee producers interested in the certification of coffee production. This work was realized with the objective to evaluate the actual situation of coffee farms, represented by a random sample of 5% of producers with respect to the adoption of good agricultural practices that include installation of coffee plantations, soil management, plant protection, harvest and post-harvest, organization management, environmental protection, and social care. The results indicate that the coffee producers of the region are conscious about the importance of using best agricultural practices, thus conditions seem favorable for the implementation of Integrated Coffee Production. This model of coffee production, implemented by the voluntary participation of producers, is timely for the organizations and its associated members to make self-assessment regarding the norm and act in the direction of economic, social and environmental sustainability.